Answer:
27
Explanation:
Set up the composite result function.
F(G(H(x)))
Evaluate F(G(H(x))) by substituting in the value of H into G.
Multiply 3 by x^2
F(G(x2))=F(3x2+2)
Evaluate F(G(x)) by substituting in the value of G into F
F(3x2+2)=2(3x2+2)-1
Simplify each term.
Apply the distributive property.
F(3x2+2)=2(3x2)+2⋅2-1
Multiply 3 by 2
F(3x2+2)=6x2+2⋅2-1
Multiply 2 by 2
F(3x2+2)=6x2+4-1
Subtract 1 from 4
F(3x2+2)=6x2+3
Evaluate the result function by replacing x with 2 in the function.
6(2)2+3
Simplify the evaluated function.
Simplify each term.
Raise 2 to the power of 2
6⋅4+3
Multiply 6 by 4
24+3
27